Pengaruh Kegiatan Eco Enzyme Terhadap Keterampilan Proses Sains Anak Usia Dini Di Taman Kanak-Kanak Ananda Maek - Aisyah Gustia, Bening; Yaswinda, Yaswinda; Zulminiati, Zulminiati; Marlina, Serli (Ar-Raihanah: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
The lack of science learning in an environment that supports the development of science process skills in early childhood is caused by a lack of teacher knowledge in introducing interesting science activities related to the environment. This study intends to demonstrate how eco enzyme activities at Ananda Maek Kindergarten affect young children's science process skills. In this study, a quantitative method and a quasi-experimental design are used. All pupils at Ananda Maek Kindergarten made up the study's population, and class B3 served as both the experimental group and class B4 served as the control group. Data analysis procedures employed normality tests, homogeneity tests, and hypothesis testing with the aid of the computerized SPSS 20. Data collection techniques used tests in the form of statements of 8 items. According to the study's findings, the pre-test sig (2-tailed) value was 0.118, and following treatment, there was a rise in both classes with a sig (2-tailed) of 0.000. However, the experimental class's average score was higher—28,400—than the control class's average of 25,80. Thus, it can be said that eco enzyme activities have a considerable impact on young children's science process skills at Ananda Maek Kindergarten.